If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -40 + -1x = -8x + 86 Reorder the terms: -40 + -1x = 86 + -8x Solving -40 + -1x = 86 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -40 + -1x + 8x = 86 + -8x + 8x Combine like terms: -1x + 8x = 7x -40 + 7x = 86 + -8x + 8x Combine like terms: -8x + 8x = 0 -40 + 7x = 86 + 0 -40 + 7x = 86 Add '40' to each side of the equation. -40 + 40 + 7x = 86 + 40 Combine like terms: -40 + 40 = 0 0 + 7x = 86 + 40 7x = 86 + 40 Combine like terms: 86 + 40 = 126 7x = 126 Divide each side by '7'. x = 18 Simplifying x = 18
| -9(5)(-1)(-1)= | | 3x+16=x+6 | | -6n+2=-5n-6 | | 1.9q-2.9-5.2q=-2.3q-2.9 | | 11x+5=247 | | x+1=5x+37 | | 2753+n=5098% | | ln(x)=3.29338 | | 6x+47=3x+22 | | 180+2.50n=1000 | | y+1=3(3-2) | | 9k=15 | | y+1=3(2-2) | | 9y-17y=-28-36 | | y+1=3(1-2) | | -(a+5)= | | 50=2*3n | | 21=9+p | | 2000000000000000000000000000000000000000+2x=40000000000000000000000000000000000000000000000000000000000000000000 | | y=dx+cwhatisd | | 42r-2(13-5r)+7=87 | | 8+5n=93 | | -57=-6(-6p-6)+3(p+8) | | (15x+7)-(9x+7)= | | 4(x-8)+2x=28 | | 21x^2-44x+20=0 | | -156+7x=-4x+75 | | -2(3s-1)-2=-2(8s+10)-2 | | 4x^2+32x+48=225 | | 1/12+(-5/6)= | | -5(3y+4)-6=-6(y+7)+3y | | -5x+4=18 |